Students' Critical Thinking and Their Writing Ability in Analytical Exposition Texts - Nasution, Putra Thoip (EXCELLENCE: Journal of English and English Education, 2025)
This study aimed to examine and explain the relationship between two variables: (1) students' critical thinking (X1) and their ability to write Analytical Exposition texts (Y). The population of this research consisted of 321 eleventh-grade students from SMAN 12 Tangerang Selatan. A random sampling technique was employed to select the sample, which included 112 students. The research instruments consisted of a critical thinking test and a writing ability test for Analytical Exposition texts. Regression and correlation analysis were used to explore the relationship between the variables. The findings revealed that (1) there was a relationship between students' critical thinking and their writing ability in Analytical Exposition texts, with a correlation coefficient of 0.231. Additionally, this relationship was categorized as weak, and the simple regression analysis showed that critical thinking contributed to writing ability in Analytical Exposition texts. The R-square value was 0.053, or 5.3%, indicating that critical thinking accounted for 5.3% of the variation in writing ability, while the remaining 94.7% was influenced by other variables not investigated in this study